ANALYSIS ONOMATOPOEIA IN SELECTED POEMS BY LEE EMMETT - Walen Carera; Anjas Anjas; Ivan Ahmad Nurcholis (Premise: Journal of English Education and Applied Linguistics, 2019)
The aims of this article are to analysis onomatopoeia with use some poems of Lee Emmett. There are five poems that have been analyzed:  running water, Bake a Cake, wind and rain, the gentle sound of rain, and See the Skater. These articles, Authors apply observation method and note taking technique. The process of this article covers several steps such as read the poems, identify, and make a table to collect Onomatopoeia word. From five poems that have been analyzed, there are two types of onomatopoeia word; primary onomatopoeia (PR) and secondary onomatopoeia (SC). Onomatopoeia found as many as 21 words. From 21words, the dominant types and meaning that used in five poems are secondary onomatopoeia; 15 words. This article is to help readers easier to understand the meaning of sound trough poems by Lee Emmet.